Applications of Silk in the Future of Medicine - A Brief Review - Archana R. Sankar; Sheela Kumar Gujjari (Current Innovations in Chemical and Materials Sciences Vol. 4, 2024)
Silk a natural protein of insect origin is produced by various breeds of silkworm. Fibroin and Sericin are the two major proteins of silk and has wide applications as biomaterials. With the diversity and control of size, structure and chemistry, recombinant silk proteins can be utilized for various biomedical applications. Though silk is used as a suture material in medicine and dentistry since time immemorial, not much light is thrown on its regenerative potential in dentistry especially periodontics. Hence this review focus on the beneficial aspects of silk and its proteins in tissue engineering.